Integrasi Program Tahfidz Al-Qur'an dan Pendidikan Formal: Dinamika Pembelajaran Santri - Irhamur Rofikoh; Herwati; Farich Purwantoro (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the learning dynamics of students in the integrated implementation of the Quran memorization program and formal education at the Nurul Huda Tahfidz Dormitory in Sentong, Probolinggo. The research problem focuses on how the integration of the two programs is implemented and the learning dynamics that arise when students must memorize the Quran while simultaneously meeting the academic demands of formal school. This study uses a qualitative approach with a case study design to gain an in-depth understanding of the phenomena occurring in the dormitory environment. The research subjects included dormitory caretakers, memorization instructors, and students participating in both programs. Data collection was conducted through observation, interviews, and documentation, while data analysis employed an interactive analysis model that encompasses data reduction, data presentation, and drawing conclusions using triangulation techniques. The results indicate that the integration of the memorization program and formal education is implemented through structured management of activities between school activities and memorization activities in the dormitory. The dynamics of student learning are influenced by self-regulation skills, time management, learning motivation, and support from the caregivers, which foster discipline, responsibility, and balance between students' academic and spiritual development